An optimal model of long-term post-stroke care - Sarzyńska-Długosz, Iwona (Frontiers in Neurology, 2023)
Stroke is a major healthcare challenge that is increasing worldwide. The burden of stroke is significant for the affected individuals as well as for the general population; high-quality care is needed to reduce its negative impacts. This article synthesized information from systematic reviews, guidelines, and primary literature on stroke care and post-stroke rehabilitation and proposes an optimal strategy for long-term post-stroke care. It also highlights the unmet needs of patients who experienced a stroke in terms of early diagnosis of complications and adequate, comprehensive therapy.